Recommendations from the COST action CA17116 (SPRINT) for the standardization of perinatal derivative preparation and in vitro testing - Janev, Aleksandar; Banerjee, Asmita; Weidinger, Adelheid; Dimec, Jure; Leskošek, Brane; Silini, Antonietta Rosa; Cirman, Tina; Wolbank, Susanne; Ramuta, Taja Železnik; Jerman, Urška Dragin; Pandolfi, Assunta; Di Pietro, Roberta; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Many preclinical studies have shown that birth-associated tissues, cells and their secreted factors, otherwise known as perinatal derivatives (PnD), possess various biological properties that make them suitable therapeutic candidates for the treatment of numerous pathological conditions. Nevertheless, in the field of PnD research, there is a lack of critical evaluation of the PnD standardization process: from preparation to in vitro testing, an issue that may ultimately delay clinical translation. In this paper, we present the PnD e-questionnaire developed to assess the current state of the art of methods used in the published literature for the procurement, isolation, culturing preservation and characterization of PnD in vitro. Furthermore, we also propose a consensus for the scientific community on the minimal criteria that should be reported to facilitate standardization, reproducibility and transparency of data in PnD research. Lastly, based on the data from the PnD e-questionnaire, we recommend to provide adequate information on the characterization of the PnD. The PnD e-questionnaire is now freely available to the scientific community in order to guide researchers on the minimal criteria that should be clearly reported in their manuscripts. This review is a collaborative effort from the COST SPRINT action (CA17116), which aims to guide future research to facilitate the translation of basic research findings on PnD into clinical practice.